Neighbourhood-Scale Carbon Footprint of Community Activities in Batu Kota, Malalayang District, Manado City - Claudhio, Jehezkiel K.; Wantasen, Sofia; Lumingkewas, Adeleyda M. W.; Paat, Frangky J.; Rotinsulu, Wiske C.; Paulus, Jeanne M.; Pakasi, Sandra E.; Pioh, Diane D.; Ogie, Tommy B.; Porong, Jelie Viekson (Sam Ratulangi University, 2026)
Neighbourhood-scale carbon-footprint assessment is increasingly important for understanding how everyday urban activities contribute to greenhouse-gas emissions. This study evaluated the carbon footprint generated by community activities in Kelurahan Batu Kota, Malalayang District, Manado City, Indonesia. The research was conducted from January to February 2026 using a quantitative survey approach with purposive sampling. A total of 335 households were selected from five neighbourhood units. Primary data were collected through field observation and questionnaires covering LPG use, household electricity consumption, motor-vehicle ownership, fuel type, and transport-fuel consumption. Carbon emissions were estimated for three activity categories, namely LPG use, electricity consumption, and motorized transportation, using IPCC-based calculation procedures. The results showed that the total carbon footprint of community activities in Kelurahan Batu Kota reached 7,410.98 ton CO₂eq year⁻¹. Transportation was the dominant emission source, contributing 4,546.12 ton CO₂eq year⁻¹ or 61.34% of the total, followed by electricity consumption at 2,432.12 ton CO₂eq year⁻¹ and LPG use at 432.74 ton CO₂eq year⁻¹. Spatially, the carbon footprint was unevenly distributed across neighbourhoods. Lingkungan 5 produced the highest total emissions at 2,646.89 ton CO₂eq year⁻¹ or 35.72% of the total, whereas Lingkungan 4 contributed the lowest share. These findings indicate that the carbon profile of Batu Kota was driven primarily by daily mobility and electricity use rather than by cooking-fuel consumption. The study provides baseline evidence for neighbourhood-based emission management and highlights the importance of place-specific mitigation strategies in urban residential environments. Keywords: carbon footprint; electricity consumption; household emissions; neighbourhood-scale assessment; urban transportation